Kesiapan Layanan Digital di UPT Perpustakaan Untan dalam Mendukung Untan Menuju Universitas Siber - Latifa, Atiqah Nur (Jurnal Ilmiah Widya Sosiopolitika; Vol 5 No 2 (2023): DIPLOMASI DAN ISU-ISU INTERNASIONAL, 2023)
In supporting Universitas Tanjungpura (Untan) towards a cyber university, Untan Library Technical Implementation Unit (UPT) prepares digital services that aims to facilitate student access to learning resources. The purpose of this research was to lead to the readiness of UPT Untan Library as the main facilitator towards a cyber university. The research method was a case study with a qualitative approach using 6 informants. Data collection techniques were semi-structured in-depth interviews, observation, and documentation studies. Data was analyzed using source triangulation. The results showed that the Untan Library was not ready to facilitate Untan towards a cyber university. Until now, digital service development has been being carried out including e-library services, e-repository, integrated master catalog, and independent uploading of student final assignments to meet the challenges of Untan's vision of becoming a cyber university which required a medium term to make it happen. It was due to constraints on the number of librarian resources and limited qualifications of information technology skills, the availability of hardware and software selection, and network reliability, therefore it obstructed the acceleration of the Untan Library following the dynamics of changing technology adaptation for the library.